Prenatal care of black women: Inequities and inequalities in the care of pregnant women - Lopes , Najila de Souza; Rocha , Iago Prina; Bastos , Norma Lopes de Magalhães Velasco; Gama , Matheus Santos; Duarte , Paloma Dias; Cunha , Caroline Valois; Lopes , Caroline Natiele de Souza; Lopes , João Vitor Machado (Seven Editora, 2023)
Introduction: The National Policy of the Black Population as a strategy to face their demands regarding injuries is a reality, but it becomes precarious when it comes to equity and accessibility. It aims to minimize inequities, vulnerabilities in the field of health and needs related to color/ethnicity. Objective: to discuss the challenges caused by inequities and inequalities in the care of prenatal parturients of black women , and to analyze the role of nursing in the monitoring of prenatal care of black women. Methods: This is an integrative literature review study, based on scientific research platforms, such as: Latin American and Caribbean Literature on Health Sciences (LILACS), Nursing Database (BDEnf), Virtual Health Library (VHL) and Scientifc Electronic Library Online (SciELO). Results and Discussion: Many studies indicate that black women are the ones who most experience violence and structural inequalities, hindering their access to social and human rights, especially sexual reproductive rights. Final considerations: In this way, it is essential to strengthen the actions that aim to improve the health of black women, emphasizing integrality, the vision of a single individual, equity and ensuring accessibility in a broad way aiming at vulnerabilities. DOI:https://doi.org/10.56238/innovhealthknow-028